neck-carean early warning system to prevent neck pain - T P, Rani.; G, Shalini; P, Sivapriya; P, Jayashri (International Journal of Engineering and Technology, 2018)
Technology has been playing a vital role in day-to-day life of the mankind. Eventually, it has also made a serious impact on the society by affecting the health condition of the people. A recent research proves that nearly 71% of the people community has been affected by the neck pain. The major factor for this impact is the long term usage of the mobiles or computers. As we are forced in an environment where we work for a very large time focusing upon a single position, there is risk of getting neck pain. To mitigate this problem, we proposed a sys-tem which alerts the user by tracking the neck movements. The sensor will be placed at the back of the user's head to determine the neck movements since the neck muscles are attached with the head. For detecting the neck movement, we have used MEMS SENSOR which can determine the variations in 3600degree. This sensor will be interfaced with the system via USB Cable through the arduino board. An alert message will be popped-out on the screen by the system to notify the user if the system finds slight variations in the neck movement. The data collected from sensor through data logging process will be sent to the registered mail of the user at the time of authentication. The sug-gestions will also be displayed as a pop-up message to reduce the strain. We have achieved approximately 93% accuracy, during testing process.Â Â Â